ANALIYSIS OF RHODAMINE B DYESTUFFS ON LIPTINT USING UV-VIS SPECTROPHOTOMETRY METHOD - wulandari, suci; Rahma, Amalia Nur; Wahyuni, Siti; Lubis, Basyariah (Jurnal FARMASIMED (JFM), 2023)
Background : Rhodamine B is a synthetic dye that is generally used as a dye for paper, textiles or inks. The use of Rhodamine B is certainly very dangerous for health. Rhodamine B if used directly on the human body will cause irritation of the respiratory tract and can cause cancer and liver damage. Although there are negative impacts, the use of these dyes is still often done, especially for food and cosmetic products. Purpose : This research was conducted to identify and determine levels of Rhodamine B in liptint traded in Lubuk Pakam sub-District. Method : Qualitative analysis of Rhodamine B was carried out by Thin Layer Chromatography (TLC) using ethylacetate-methanol-ammonia (45:25:30), while quantitative analysis for assay was carried out using UV-VIS Spectrophotometry at a wavelength of 545 nm. The linear calibration curve in the range of 1 - 5 ?g /ml resulted in the regression equation y = 0.0091x - 0.009. Results : The results of the qualitative analysis showed that the three samples containing Rhodamine B with each Rf value of 0.87 cm (sample A), 0.96 cm (sample B), 0.98 cm (sample C) and quantitatively the levels for sample A were known is 13,144 mg/g, sample B is 27,704 mg/g and sample C is 20,386 mg/g. Conclusion : From this research, it is known that there is still the use of Rhodamine B as a dye in liptint traded in Lubuk Pakam sub-district